Respectus Philologicus, 2009 Nr. 16 (21) A - Bankauskaitė, Gabija (Respectus Philologicus, 2009)
CONTENTS I. DISCOURSE: THE RESEARCH PROBLEMS OF GENERATION, PERCEPTION AND IMPACT Agnieszka Miksza (Poland). The Politics of Reading and Writing. Jeanette Winterson’s Dialogue with Herself and the Reader... 11 Olga Glebova (Poland). Recontextualisation as an Interpretive Strategy in Contemporary Novelistic Discourse ... 19 Wojciech Majka (Poland).Understanding as Context for Disclosure ... 30 Jurgita Vaičenonienė (Lithuania). Cultural Translation and Linguistic Metaphor: A Case Study of Verbal Metaphor Translation ... 38 Regina Koženiauskienė (Lithuania). The Manipulation of Headlines: The Opposition of Text and Context... 50 Erika Rimkutė, Neringa Pakalnytė (Lithuania). Topics and Linguistic Features of Social Advertisements...57 Dovilė Vengalienė (Lithuania). The Cultural Aspects of Auto-Ironic Blends Referring to Lithuania and America in News Headlines ... 73 Solveiga Sušinskienė (Lithuania). Nominalization as a Micro-Structural Item of English Scientific Discourse ...84 II. LITERARY FICTION: INTERPRETATION POSSIBILITIES Ugnius Keturakis (Lithuania). Two Ways Leading to Modern National Culture: Vincas Kudirka and Jurgis Baltrušaitis... 93 Marek Smoluk (Poland). The English Royal Court through the Eyes of Erasmus ... 105 Ingrida Žindžiuvienė (Lithuania). Location and Space in Don Delillo’s Cosmopolis and Antanas Škėma’s Balta drobulė ... 112 III. CONTEMPORARY RESEARCH INTO LITHUANIAN LINGUISTICS: LINGUISTIC AND EXTRALINGUISTIC APPROACHES Jonas Andrijauskas, Lina Bačiūnaitė-Lužinienė, Vytas Kriščiūnas (Lithuania). The Employment of New Technologies in Diachronic Toponymy ... 123 Saulė Juzelėnienė, Giedrė Baranauskaitė (Lithuania). The Expression of Semantic Group of Movement in the Air in the Lithuanian and English Languages... 135 Robertas Kudirka (Lithuania). The Formant Structure of the Accented Long and Short Vowels in the Lithuanian Standard Language... 141 Jurga Kerevičienė (Lithuania). Dativus iudicantis in Lithuanian and its Equivalents in English ... 153 Daiva Aliūkaitė (Lithuania). Accuracy of Standard Language Images: the Problem of Quasistandard... 160 Nijolė Tuomienė (Lithuania). Declension of the ā- and iā Stem nouns in the Peripheral Ramaškonys Subdialect... 188 Rima Bacevičiūtė (Lithuania). Tendencies and problems of instrumental analysis of sounds in lithuanian dialectology... 202 IV. SCIENTIFIC LIFE CHRONICLE Birutė Briaukienė (Lithuania). 110 Years to “Lietuviška gramatikėlė”...216 Daiva Aliūkaitė, Gabija Bankauskaitė-Sereikienė (Lithuania). Young Linguists of the Lithuanian Language Gathering — a Part of Jubilee Events at VU KHF ...221 V. REQUIREMENTS FOR PUBLICATION... 226 VI. OUR AUTHORS... 234